Knowledge Level of Silkworm Rearers of Jammu Division of Jammu and Kashmir State (Indian Journal of Extension Education, 2016)
The present study was carried out to know the knowledge level of silkworm rearers of Jammu division. The study revealed that from three districts 60.00 per cent of respondents had medium knowledge followed by 32.92 per cent respondents had low knowledge and 15.36 per cent respondents had high knowledge respectively. The overall mean knowledge score was 15.36 (+ 2.29). Majority of respondents (93.33%) had knowledge of time of pruning, (82.91%) of respondents had knowledge of insects of mulberry plants,(90.41%) and (83.75%) had knowledge of methods of disinfecting the silkworm body and rearing seat and disinfectants used for rearing room and appliances, (95.41%), (82.91%) and (78.75%) had knowledge of control of insect/pest of silkworm, management of diseases, insect pest of silkworm and important diseases of silkworms, (88.75%) and (83.26%) had knowledge of late age silkworm rearing techniques and low cost devices for cocoon stifling, low percentage of respondents had knowledge of length and thickness of mulberry cuttings for propagation and only (27.08%) respondents had knowledge of improved variety of mulberry, Less percentage of respondents had knowledge of method of silkworm incubation, temperature cum humidity requirement for young as well as late age rearing.